Institutional Model of Counseling in the Costa Rican Public Education System - Gamboa Jiménez, Alejandra (2021)
This article includes reflections on the disciplinary model of Educational Counseling in the public educational system of Costa Rica, an analysis within the framework of the project Counseling Models from the Viewpoint of the Professional Performance Profile of the Universidad Nacional, Costa Rica, a system highlighted by the diversity of centers, modalities, levels, and the multiple characteristics of the population it assists. Methodologically, the phenomenological design is used, contemplating both interviews with specific people in the context under study and triangulation to interlink empirical data and hiring profiles, for which the use of the tool AtlasTi tool contributed to the organization of the data. It is a conclusion that the institutional model of Educational Counseling in the Ministry of Public Education (MEP, for its acronym in Spanish) is intersected between the jurisprudential scaffolding that shapes the action of the modalities, levels, and specific context of each educational center and the demands of professional practice both for compliance with the technical guidelines issued by MEP and those that arise from emerging disciplinary situations of everyday work.